Chemotaxonomy studies on the genus Hedysarum. (October 2019) - Liu, Yi; Yang, Hongshuai; Liu, Yi; Wang, Wei; Zhao, Yuying; Chen, Hubiao; Liang, Hong; Zhang, Qingying
Abstract: In combination with phytochemical results, the pilot chemotaxonomy study on genus Hedysarum by using HPLC methods revealed differences between section Fruticosa and the three other sections Multicaulia, Obscura and Subacaulia, but there was a closer genetic relationship with Multicaulia and Subacaulia . Isoflavonoids and pterocarpans were proved to be the common constituents of genus Hedysarum, whereas pterocarpans, benzofurans, and coumestans were the characteristic constituents of section Fruticosa, and chalcones were the chemical markers of section Multicaulia and section Subacaulia . The present finding is consistent with the classical morphological classification of genus Hedysarum, and provides supporting evidences for dividing Hedysarum into two subgenera, i.e. subgenus Hedysara and subgenus Ruticosa . Highlights: Sect. Fruticosa was much different from the three other sections, while sect. Multicaulia was closer to sect. Subacaulia. Isoflavonoids and pterocarpanes were proved to be the common constituents of genus Hedysarum. Pterocarpenes, benzofurnans, and coumestans were the characteristic constituents of sect. Fruticosa. Chalcones were the chemical marks of sect. Multicaulia and sect. Subacaulia.